HIGH PRECISION CALCULATION OF MOVE OUT CORRECTION IN GPR MEASUREMENTS - Janis Karuss (European Scientific Journal, ESJ, 2014)
Ground penetrating radar (GPR) is a non-invasive geophysical method that can be used in shallow subsurface exploration. Using GPR it is possible to make high precision measurements of thickness of deposit layer and its distribution in research area. In cases when GPR measurements are performed by bistatic antenna system, time intervals after which reflected signals are received usually are measured relatively to arrival of direct signal. As a result the precise time interval that is necessary for signal to travel from antenna system to reflector is unknown. This paper provides description of precise move out correction value determination experiment and calculation method. Recommended method was tested on 3 different bogs in Latvia (Cenas tīrelis bog, Dzelves bog and Ķūķi bog). The main conclusions of described research are: Traditional method of move out correction calculation is inaccurate in cases when GPR antenna systems in process of radiolocation profiling are in direct contact with the ground surface. Suggested method of move out correction calculation is easy performable and gives accurate results.